PENGEMBANGAN MODUL MATAKULIAH STATISTIKA DAN PROBABILITAS BERBASIS KONTEKSTUAL - Maulana, Charis (Jurnal Pengembangan Rekayasa dan Teknologi, 2023)
Mathematics is one of the components from a series of subjects that has an important role in education. Mathematics learning aims to equip students to be able to think critically, logically, and practically, as well as be positive and have a creative spirit in problem solving within various fields. One of the mathematics courses studied in various study programs is statistics and probability. Currently, many modules are used in learning, but these modules have not been able to help students understand these courses. For that reason, we need a development of learning tools in the form of modules that help students understand statistics and probability courses. One approach that can be used in developing statistics and probability modules is the contextual approach. The contextual approach is the linkage of each material or learning topic with real life. Contextual Teaching Learning (CTL) is a holistic learning process that aims to teach students to understand teaching materials in a meaningful way that is associated with real life contexts, whether related to personal, religious, social, economic, and cultural environments. By using contextual based modules, it is expected that students can indirectly apply statistics and probability material in real life or according to the field of science they are learning.
Keywords: Modul; Pendekatan Kontekstual; Statistika dan Probabilitas